Retrospective Analysis of Childhood Hepatoblastoma in a Single Centre in China. Issue 7 (July 2019) - Wang, T.Y.; Han, Y.L.; Gao, Y.J.; Xu, M.; Gu, S.; Yin, M.Z.; Zhong, Y.M.; Hu, W.T.; Pan, C.; Tang, J.Y.
Abstract: Aims: To investigate the protocol efficacy and prognostic factors for paediatric hepatoblastoma in a multidisciplinary model in our centre. Materials and methods: Consecutive hepatoblastoma patients (<18 years old) treated at Shanghai Children's Medical Center in China from August 2011 to October 2017 were analysed retrospectively for clinical features, chemotherapy courses, surgical treatment and outcomes. Results: One hundred and four cases of paediatric hepatoblastoma (64 males, 40 females; median age at diagnosis 1.64 years) had a median follow-up of 30.68 months (range 8.3–73.3 months). First complete remission was achieved in 95 cases, 85 of which achieved continuous complete remission. Another three cases were lost to follow-up after a median of 24.73 months in complete remission. Seven cases relapsed later, with two achieving a second complete remission and four deaths. Nine cases did not achieve complete remission and five of them died. In general, the 5-year overall survival rate and 5-year event-free survival (EFS) rate were 86.3 ± 5.0% and 81.8 ± 4.3%, respectively. Thirty-two cases were classified as standard risk and 72 as high risk with 5-year EFS of 96.8 ± 3.2% and 75.7 ± 5.7% ( P = 0.029) and 5-year overall survival of 100% and 80.5 ± 7.0%, respectively. The mean platelet count ( P = 0.0036), lactate dehydrogenase ( P = 0.0443) and ferritin level ( P = 0.0006) at diagnosis were much higher in the high-risk group than in the standard-risk group. Univariate analysis showed that patients <5 years of age ( P = 0.018), with higher α-fetoprotein (AFP) level (>100 ng/ml, P = 0.008), without metastases at diagnosis ( P = 0.001) and postoperative AFP recovery after no more than three chemocycles ( P = 0.014) had better overall survival. In addition, the above factors, except metastases at diagnosis and risk group, were associated with prognosis in the multivariate analysis. Conclusions: The result of this protocol had similar overall survival and EFS rates compared with those in developed countries. Normal postoperative AFP levels after three chemocycles has prognostic value. Highlights: The 5-year overall and event-free survival rates of this protocol were 86.3% and 81.8% for paediatric hepatoblastoma patients. The mean platelet count, lactate dehydrogenase and ferritin levels at diagnosis were much higher in the high-risk group. Normal postoperative α-fetoprotein levels after three chemocycles have a prognostic value.